Advanced Mathematical Modeling and Numerical Solutions in Applied Mechanics and Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint encompasses articles that were accepted and published as part of the Special Issue entitled “Advanced Mathematical Modeling and Numerical Solutions in Applied Mechanics and Engineering.” This Special Issue delves into the theory and application of mathematical models across various disciplines. We hope that these publications can inspire researchers in relevant communities. It is our aim that these papers will not only stimulate future research in mathematical models and numerical methods but also encourage the exploration of their potential applications.